1960
DOI: 10.1161/01.cir.22.2.289
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure in Bushmen of the Kalahari Desert

Abstract: The blood pressure was studied in 42 males and 36 females in 2 groups of nomadic Bushmen, living near Ghanzi in the Kalahari Desert, as well as in a third group of 21 Bushmen prisoners and farm laborers from the same region. The pressures were also "corrected" for arm girth. The average systolic pressures were 108.4 mm. Hg (S.D. 11.4) for men and 112.8 mm. Hg (S.D. 14.6) for women. The average diastolic pressures were 66.2 mm. Hg (S.D. 6.9) and 69.6 mm. Hg (S.D. 8.0) for men and women, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…An important article in Circulation describes the blood pressure (BP) patterns of this group in 1960. 10 Quite differently from the pattern in most Western persons, the BP did not rise with age. This poses the repetitive problem, do the differences lie in the genes or the environment?…”
Section: Early Tribal Lifementioning
confidence: 85%
“…An important article in Circulation describes the blood pressure (BP) patterns of this group in 1960. 10 Quite differently from the pattern in most Western persons, the BP did not rise with age. This poses the repetitive problem, do the differences lie in the genes or the environment?…”
Section: Early Tribal Lifementioning
confidence: 85%
“…In Kalahari Desert Bushmen and Central African Pygmies, observers could not find any case of high blood pressure and blood pressure did not increase with age (335,349) . Dental surveys of Kalahari Bushmen (350) and other hunter -gatherers (49) showed a remarkable absence of caries.…”
Section: Anthropologymentioning
confidence: 99%
“…Several studies performed in Africa also suggested that hypertension was rare in African populations, although in some cases this was thought to relate to poor nutrition and sarcopenia. [65][66][67] However, it is striking that early studies in Bantu-speaking groups reported unusually high frequencies of hypertension, many of whom went on to develop kidney disease. 68,69 Renal biopsy studies confirmed that the primary lesion was of severe arteriolosclerosis with secondary glomerulosclerosis, lesions that can occur with severe primary hypertension.…”
Section: A Genetic Basis For Hypertension and Kidney Disease: Role Ofmentioning
confidence: 99%